RETRACTED: When Words Hurt: Affective Word Use in Daily News Coverage Impacts Mental Health - Wormwood, Jolie B.; Devlin, Madeleine; Lin, Yu-Ru; Barrett, Lisa Feldman; Quigley, Karen S. (Frontiers in Psychology, 2018)
Media exposure influences mental health symptomology in response to salient aversive events, like terrorist attacks, but little has been done to explore the impact of news coverage that varies more subtly in affective content. Here, we utilized an existing data set in which participants self-reported physical symptoms, depressive symptoms, and anxiety symptoms, and completed a potentiated startle task assessing their physiological reactivity to aversive stimuli at three time points (waves) over a nine-month period. Using a computational linguistics approach, we then calculated an average ratio of words with positive vs. negative affective connotations for only articles from news sources to which each participant self-reported being exposed over the prior two weeks at each wave of data collection. As hypothesized, individuals exposed to news coverage with more negative affective tone over the prior two weeks reported significantly greater physical and depressive symptoms, and had significantly greater physiological reactivity to aversive stimuli.